دینِ اسلام کے مذہبی تہوار و رسوم کا پس منظر دینیاتی مصادر کی روشنی میں:ایک تحقیقی جائزہ (Al-Qamar, 2020)
Islam is a perfect religion. It teaches its followers good manners step by step. In addition to the acts of worship in life, there are various festivals and rituals in Islam which are proved by the Qur'an and Hadith and the Companions of the Holy Prophet (PBUH).From the Qur'an and Hadith, only two festivals have been proved, one is Eid-ul-Fitr and the other is Eid-ul-Adha. But nowadays various festivals are attributed to Islam which is a total oppression of Islam. This article is written to expose such fabricated festivals and rituals and to examine them in the light of the religious sources of Islam.
Keywords: Islam; festivals; the Holy Qur'an and Hadith; Eid-ul-Fitr; Eid-ul-Adha